Make Healing, not Performance, the Goal for K-12 Schools Amid this Global Pandemic - Munyi Shea; Alexis N. Awdziejczyk (International Dialogues on Education: Past and Present, 2020)
The novel coronavirus (COVID-19) has had far reaching implications on every aspect of human life – from where we work, to where we feel safe to grocery shop, to how we greet friends. At the same time, the pandemic has exposed long-standing issues of structural racism, xenophobia, social and economic inequities, precipitating multiple large-scale social justice movements and demonstrations in the United States, culminating in “dual public health emergencies.” As Kindergarten through Grade 12 (K-12) students slowly return to school, educators are grappling with how to support their students amid these overlapping crises. In this paper, we discuss the relevance of trauma-informed pedagogy, with a specific focus on 3Rs – relational connectedness, restored trust, and contextualized resilience. We urge educators to keep the whole child at the center of their curriculum, and to make healing – not performance – the priority for K-12 schools amid and following the global pandemic.